Can the characteristics of the sharia supervisory board increase the trust of sharia bank customers? - Dini Dewindaru; Ermina Sari (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study aims to examine in more detail the characteristics of SSB that will affect the level of trust of Islamic banking customers. The purpose of this study is to understand empirically the relationship between the characteristics of SSB and the trust of Islamic bank customers in Indonesia.Method - A quantitative approach with the panel data analysis method is used to analyze sample data from all Sharia commercial banks in Indonesia in the 2012-2019 period. The independent variable in this study consisted of 6 characteristics of SSB.Result - The results of the study show the facts that the 3 characteristics of SSB are proven to be able to increase customer trust. The three variables are the number of members, financial expertise, and doctoral education.Implication - Islamic Commercial Banks in Indonesia suggest to put more consideration of the number of members, financial expertise, and doctoral education in the recruitment process for the selection of Sharia bank SSB members.Originality - In contrast to previous research which examines the effect of the existence of SSB on customer trust and loyalty, this study seeks to get deeper answers to the input factors of SSB characteristics that really have a positive impact on a positive image and customer trust in Islamic banks.